2012
DOI: 10.4149/bll_2012_001
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus inhibits intimal hyperplasia in arterialised veins in rats

Abstract: Abstract:Objectves: We investigated whether tacrolimus (FK506) can inhibit neointimal formation in arterialised vein grafts in rats. Methods: Lewis iliolumbar veins were implanted into the abdominal aorta of isogeneic rats. Animals in the treatment groups had daily intramuscular injections of tacrolimus at 0.2 mg/kg (group B) and 0.1 mg/kg (Group C), respectively. The control group A had no treatment. Light microscope evaluations of arterialised vein grafts were performed 30 days after operation. We determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…This dose led to blood concentrations of 5 ng/ml. Moreover, we confirmed that this low blood concentration inhibits intimal hyperplasia in arterialised syngeneic veins in our previous study,[29] and inhibited histological signs of allogeneic vein rejection [12].…”
Section: Discussionsupporting
confidence: 90%
“…This dose led to blood concentrations of 5 ng/ml. Moreover, we confirmed that this low blood concentration inhibits intimal hyperplasia in arterialised syngeneic veins in our previous study,[29] and inhibited histological signs of allogeneic vein rejection [12].…”
Section: Discussionsupporting
confidence: 90%